2016
DOI: 10.1519/jsc.0000000000001096
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral vs. Bilateral Squat Training for Strength, Sprints, and Agility in Academy Rugby Players

Abstract: The purpose of this study was to investigate the effects of a 5-week lower-limb unilateral or bilateral strength program on measures of strength, sprinting, and change of direction speed. Eighteen academy rugby players (18.1 ± 0.5 years, 97.4 ± 11.3 kg, 183.7 ± 11.3 cm) were randomly assigned to either a unilateral (UNI) or bilateral (BI) group. The UNI group squatted exclusively with the rear elevated split squat (RESS), whereas the BI group trained only with the bilateral back squat (BS). Both groups trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
113
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 30 publications
(48 reference statements)
8
113
2
1
Order By: Relevance
“…This pilot study successfully demonstrated that an investigation between the squat, deadlift, and hip thrust is feasible; in addition, this present study provides effect-sizes from which 16,18 , such a conclusion cannot be directly drawn from pilot data.…”
Section: Discussionmentioning
confidence: 78%
“…This pilot study successfully demonstrated that an investigation between the squat, deadlift, and hip thrust is feasible; in addition, this present study provides effect-sizes from which 16,18 , such a conclusion cannot be directly drawn from pilot data.…”
Section: Discussionmentioning
confidence: 78%
“…To run faster, the individual must be able to transfer their general strength to the sprint step by ensuring that the nervous system can control the augmented force output (Tsimahidis et al, 2010). This could result in greater force and power generation within the sprint step, and indeed strength and power training can improve speed (Lockie, Murphy, Schultz, Knight, & Janse de Jonge, 2012;Speirs, Bennett, Finn, & Turner, 2016). To increase the specificity of resistance training for speed development, it is important to incorporate unilateral exercises (Lockie et al, 2012;Speirs et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This could result in greater force and power generation within the sprint step, and indeed strength and power training can improve speed (Lockie, Murphy, Schultz, Knight, & Janse de Jonge, 2012;Speirs, Bennett, Finn, & Turner, 2016). To increase the specificity of resistance training for speed development, it is important to incorporate unilateral exercises (Lockie et al, 2012;Speirs et al, 2016). One example of a unilateral strength exercise is the Bulgarian split-squat (BSS), which involves an individual performing a single-leg squat while the non-working leg is supported on a bench (McCurdy, Langford, Cline, Doscher, & Hoff, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that both unilateral and bilateral squat training can improve lower body strength, sprint speed, and agility in individuals. 1 Both unilateral and bilateral squats are also used as assessments of dynamic lower-extremity motor control. [2][3][4][5][6][7] The utility of unilateral and bilateral squats for training and assessment has made these movements a foundational part of athletic and exercise training programs.…”
mentioning
confidence: 99%